Identification and Characterization of microRNA319a and Its Putative Target Gene, PvPCF5, in the Bioenergy Grass Switchgrass (Panicum virgatum) - Xie, Qi; Liu, Xue; Zhang, Yinbing; Tang, Jinfu; Yin, Dedong; Fan, Bo; Zhu, Lihuang; Han, Liebao; Song, Guilong; Li, Dayong (Frontiers in Plant Science, 2017)
Due to its high biomass yield, low environmental impact, and widespread adaptability to poor soils and harsh conditions, switchgrass (Panicum virgatum L.), a warm-region perennial herbaceous plant, has attracted much attention in recent years. However, little is known about microRNAs (miRNAs) and their functions in this bioenergy grass. Here, we identified and characterized a miRNA gene, Pvi-MIR319a, encoding microRNA319a in switchgrass. Transgenic rice lines generated by overexpressing the Pvi-MIR319a precursor gene exhibited broader leaves and delayed flowering compared with the control. Gene expression analysis indicated at least four putative target genes were downregulated. Additionally, we cloned a putative target gene (PvPCF5) of Pvi-MIR319a from switchgrass. PvPCF5, a TCP transcription factor, is a nuclear-localized protein with transactivation activity and control the development of leaf. Our results suggest that Pvi-MIR319a and its target genes may be used as potential genetic regulators for future switchgrass genetic improvement.